Safety and Efficacy of All-In-One Percutaneous Pedicle Screw System. Issue 4 (May 2023) - Kojima, Atsushi; Aihara, Takato; Urushibara, Makoto; Hatakeyama, Kenji; Sodeyama, Tomonori
Study Design: Retrospective study of the prospectively collected outcomes data. Objective: The indications for PPS placement during minimally invasive spine stabilization (MISt) procedures have increased in recent years. To the best of our knowledge, no studies have documented the outcomes of PPS insertion using the all-in-one PPS system. This study compared the conventional methods and the use of all-in-one percutaneous pedicle screw (PPS) system with respect to the speed and accuracy of PPS placement. We also determined the advantages associated with the use of the all-in-one PPS system. Methods: We evaluated 54 patients who underwent PPS insertion using the conventional method and the all-in-one PPS system during MISt procedures. We also assessed the number of implanted PPSs, the time taken to implant PPSs, and the accuracy of PPS placement based on postoperative computed tomography images. Results: A total of 254 PPSs were inserted (126 using the conventional method and 128 using the all-in-one PPS system). The PPS insertion time with the all-in-one PPS system (mean, 25.3 ± 9.1 s) was significantly shorter than that using the conventional method (mean, 63.1 ± 13.0 s; P < 0.01). With respect to the accuracy of PPS insertion, ≥ 2 mm pedicle breach was noted in one case each in both groups. Conclusions: PPS placement using the all-in-one PPS system is as safe as conventional methods and has the potential to save the surgical time of MISt procedures.